Anti-Anxiety and Antidepressant Activity of Ethanolic Extract of Dalbergia Sissoo for Anxiety and Depression in Ovariectomized Rats - Vaidya, Mrunal Mukesh; Kolhe, Swati; Tembhurne, Sachin (Journal of Drug Delivery and Therapeutics, 2019)
There are studies showing the effects of long-term ovarian hormones withdrawal and post-menopause on animal behavior. Ovarian hormones play a critical role is modulating anxiety and depressive symptoms in female. Thus, this current study evaluated the anxiety and depression of long-term ovariectomy (OVX) in adult rats subjected to the light and dark chamber and forced swimming tests. In this study, we tested the effect of hydroalcoholic extract of Dalbergia sissoo on female anxiety and depression in long-term postsurgical bilateral ovariectomized female rats. 6-month old female Wistar rats were used and distributed in 5 groups; diestrus rats, ovariectomized (OVX) groups with 60 days, OVX treated with standard β Estradiol (0.1mg/kg/s.c), OVX treated hydroalcoholic extract of Dalbergia sissoo (200 & 400 mg/kg). All treatments were given for further 28 days after post-surgical period (60 days) in ovariectomized female rats. They were evaluated on the 28th day in the light and dark chamber and forced swim test apparatus. The treatment of the hydroalcoholic extract of Dalbergia sissoo (200 and 400 mg/kg) in the OVX rats shows significant increase in the time spent in the light chamber and the immobility time was significantly decrease in the extracted treated groups as compared to the OVX group. Anxiety-like and depressive-like behaviors were observed in rats which were influenced by post-menopause or ovarian hormone withdrawal. Results suggested that 28 days of treatment with hydroalcoholic extract of Dalbergia sissoo is able to lower the anxiety levels and depression in estrogen deficient females.Keywords: Dalbergia sissoo, Post menopause, Anxiety, Depression, Light dark box, Forced swim test.